Professional and public views about early return of patients from Comprehensive Stroke Centers to local Acute Stroke Centers in England following displacement by emergency care pathways - Price, Chris; Zhu, Becky; Alton, Abigail; Ford, Gary A.; James, Martin; McClelland, Graham; White, Phil; Shaw, Lisa (Frontiers in Stroke, 2024)
Background: Mechanical thrombectomy is a highly effective emergency treatment for selected cases of ischaemic stroke but can only be provided at hospitals with appropriate facilities and interventionists. Many patients require transfers for treatment, including some who are subsequently considered ineligible. To maintain capacity at thrombectomy centres, displaced patients should soon be returned to their local hospital following assessment and treatment, but return processes vary. We sought the views of stroke and ambulance services, clinicians and public representatives about the timing, planning and implementation of acceptable processes to inform recommendations about the early return of patients (<24hrs) displaced as a result of thrombectomy pathways. Methods: Three workstreams were undertaken between 01/05/2023 and 31/10/2023: 1. An online survey of hospital stroke services supplemented by a convenience poll of stroke clinicians 2. An online survey of ambulance services 3. Focus groups with stroke patients and carers using a topic guide describing typical early return scenarios. The surveys used multiple choice answers supplemented by free text boxes for additional comments. Data were reported descriptively without statistical comparison. Focus group data were analysed thematically using emergent coding. Results: Responses were obtained from 32 stroke services, 44 stroke clinicians and 11 ambulance services. Stroke service and clinician respondents generally supported early return for most clinical scenarios but advised caution regarding transfers <4hrs after thrombectomy and <24hrs for haemorrhagic stroke due to the higher risk of complications. Ambulance respondents highlighted travel time, immediate service pressures and crew type as influences upon providing early returns, but supported 24/7 provision. Twenty-nine patients and four carers participated in three focus groups. There was general acceptance of early return processes but these participants emphasized the need for clear communication and individualised decisions based upon clinical status, age, journey length, patient preferences and individual contextual factors. Conclusions: All contributors were generally supportive of early patient returns to maintain thrombectomy centre capacity, but the results suggest important organisational, clinical and patient focussed considerations for successful implementation.